Dorongan Psikis Tokoh pada Novel Ayat-Ayat Cinta 2 Karya Habiburrahman El Shirazy (The Psikis Drive of the Characters of Ayat-Ayat Cinta 2 Novel By Habiburrahman El Shirazy) - Abdul Rozak; Atikah Atikah; Diana Rahmawati Rozak (Indonesian Language Education and Literature, 2021)
The purpose of this study was to describe the concept of psychic impulses in the characters in the novel Ayat-Ayat Cinta 2 by Habiburrahman El Shirazy. This study uses a qualitative method with a descriptive-analytical working mechanism. The approach used is a literary psychology approach. The data collection technique applied is documentation. The data analysis activities consist of data reduction, data presentation, and concluding/verification. The results of the study indicate that there is an impetus that drives or underlies the behaviour of each character. Interaction between characters leads to encouragement, namely encouragement that comes from the spiritual aspect, encouragement to fulfil desires without regard to values, and encouragement that is influenced by news in the mass media. Changes in the character of the antagonist are influenced by the behaviour of practising the Qur'an and hadith by the main character. Thus, reflected in the pattern of the relationship between individual history, goals, and aspirations of individuals to the behaviour of the characters.Tujuan penelitian ini adalah untuk mendeskripsikan konsep dorongan psikis pada tokoh dalam novel Ayat-Ayat Cinta 2 karya Habiburrahman El Shirazy. Penelitian ini menggunakan metode kualitatif dengan mekanisme kerja deskriptif analitik. Pendekatan yang digunakan adalah pendekatan psikologi sastra. Teknik pengumpulan data yang diaplikasikan adalah dokumentasi. Aktivitas analisis data tersebut terdiri atas reduksi data, penyajian data, dan penarikan kesimpulan/verifikasi. Hasil penelitian menunjukkan bahwa terdapat dorongan yang menggerakkan atau melatarbelakangi perilaku setiap tokoh. Interaksi antartokoh mengarah pada adanya dorongan, yakni dorongan yang berasal dari aspek spiritualitas, dorongan memenuhi keinginan tanpa memperhatikan nilai-nilai, dan dorongan yang dipengaruhi oleh pemberitaan di media massa. Perubahan karakter tokoh antagonis dipengaruhi perilaku pengamalan Al-Qur’an dan hadis oleh tokoh utama. Dengan demikian, tercermin adanya pola hubungan antara sejarah individu, tujuan, dan aspirasi individu terhadap perilaku tokoh.